Characteristics affecting the use of imagery: A Youth Sports Academy study - Parker, J. K.; Lovell, G. (Journal of Imagery Research in Sport and Physical Activity, 2009)
An understanding of the effects of imagery on performance is well documented (Weinberg, 2008). However, most of the research has been conducted examining adult athletes (Hall, 2001); few studies have investigated the characteristics of youth sport performers imagery use. Participants from a United Kingdom sports academy included 74 individuals (42 male, 32 female), with a mean age of 16.76 (SD = 0.72). The sample included 24 national, 23 county, and 27 club athletes from a total of 13 sports. Participants completed the Sport Imagery Questionnaire (SIQ; Hall et al., 1998) and the Vividness of Movement Imagery Questionnaire (VMIQ; Issac et al., 1986). Participants were grouped according to competitive level, practice volume, and imagery ability. Results indicated that athletes use motivational general-mastery imagery most frequently with motivational general-arousal used the least. There was also a significant difference between practice volume and subsequent imagery use. The results suggest that applied practitioners' working with youth sport performers should consider practice volume as a potential characteristic that influences the frequency of imagery use.